Aedes Aegypti Larva Density in Angin Nauli Village, North Sibolga District - Manotar Sinaga; Crishartanto Simanungkalit (Institute of Computer Science (IOCS), 2020)
Dengue fever is a public health problem in Indonesia with high morbidity and mortality and has the potential to cause extraordinary events (KLB) and / or epidemics as well as to impact the economic loss of society. Dengue fever is a vector-borne disease. Dengue fever contributed 204,171 (47.87%) of the number of sufferers due to five vector-borne and zoonotic diseases in Indonesia in 2016 and ranks second after malaria. Efforts to eradicate mosquito vectors can be carried out through eradication of mosquito nests (PSN). The high density of Aedes aegypti mosquitoes has a high risk of transmitting mosquitoes for dengue transmission. Larva Free Rate (ABJ) is a measure of vector eradication efforts through the PSN-3M showing the level of community participation in preventing dengue. Sibolga City is one of the municipalities in North Sumatra Province. Sibolga City consists of 4 districts. The number of dengue cases in Sibolga City in 2016 was 103 cases, where the highest cases were in North Sibolga District, with 40 cases (4). This type of research uses descriptive method. This descriptive study aims to determine the density of aedes aegypti larvae. Time and place of research The research was conducted in August - November 2020 in Angin Nauli Village, North Sibolga District. The population and samples are all houses that have containers in Angin Nauli Village. Sampling was done by total sampling. The number of households in Angin Nauli Village is 858 households. This research should be useful for future researchers, and it is suggested to be a reference for the same research with a larger number of samples and in different places.